2007
DOI: 10.1158/1078-0432.ccr-07-1369
|View full text |Cite
|
Sign up to set email alerts
|

p53 Mutations in Deep Tissues Are More Strongly Associated with Recurrence than Mutation-Positive Mucosal Margins

Abstract: Purpose: Application of ultrasensitive diagnostics has shown that small numbers of p53 mutation-positive cells may signify the presence of residual tumor in histologically normal tissues after resection of squamous cell carcinomas arising in the head and neck area. To date, most studies in this area have focused on analysis of tissues at the mucosal aspect of the resection and highlighted the importance of molecular changes in the field with respect to the risk of recurrence. Experimental Design: In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Some groups, therefore, investigated alternative approaches to the detection of occult tumor cells in the surgical margins of patients with HNSCC [9,10]. These occult tumor cells may express factors associated with local recurrence and some of these factors, which are the result of genetic or epigenetic alterations, can be detected by IHC staining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some groups, therefore, investigated alternative approaches to the detection of occult tumor cells in the surgical margins of patients with HNSCC [9,10]. These occult tumor cells may express factors associated with local recurrence and some of these factors, which are the result of genetic or epigenetic alterations, can be detected by IHC staining.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in p53 have commonly been found in HNSCCs, but its influence on prognosis remains controversial. In recent reports, p53 mutations, detected by molecular assays such as DNA sequencing, LigAmp assay, and real-time PCR, were considered a useful prognostic factor [9][10][11][12]. However, we previously reported that the IHC assay of p53 was not useful in predicting the prognoses of patients undergoing chemoradiation therapy [13].…”
Section: Discussionmentioning
confidence: 99%
“…Translational research, based on the application of molecular diagnostics to detect residual tumour after surgery for head and neck carcinoma, has highlighted the need to identify treatment modalities, other than radiotherapy, to prevent recurrence at the operative site (Huang et al, 2007). Vascular endothelial cell growth factor signalling inhibitors are attractive for the treatment of residual disease, as tumour regrowth is dependent on neovascularisation, and in this report, we show that ZD4190 can prevent outgrowth of malignant cells when the tumour burden is below a critical threshold.…”
Section: Discussionmentioning
confidence: 99%
“…This is important as the term surgical margins frequently causes confusion, as it may be wrongly assumed that the tissues examined are taken from the edge of the resected carcinoma, rather than from the normal tissues. Analysis of both mucosal and deep 'molecular margins' has revealed that the finding of p53 mutations in deep margins is more strongly associated with development of local recurrence than p53-mutation-positive mucosal margins (Huang et al, 2007). A second key observation that has emerged from all studies applying these new diagnostics (Brennan et al, 1995;Partridge et al, 2000Partridge et al, , 2005van Houten et al, 2002van Houten et al, , 2004Huang et al, 2007) is that multiple tumour-positive margins are associated with local recurrence, indicating that local spread is more widespread than envisaged earlier.…”
mentioning
confidence: 99%
“…[20] Similar studies on adjacent normal mucosal alterations by evaluating p53 expression revealed high incidence of TP53 mutations in histologically tumor-free surgical margins. [21] Further, studies on molecular characteristics of tumor-free surgical margins confi rm genotypic alterations on the basis of loss of heterozygosity (LOH), [22] thus, evaluating early biological alterations in the mucosa adjacent to cancerous lesions is very essential for the pathologists to minimize recurrences. These fi ndings suggest AgNORs might be a valuable complement to classical histology in oral cancers.…”
Section: Number Of Profi Les Of Agnor Per Nucleus (N Nor)mentioning
confidence: 99%